2021
DOI: 10.3390/jpm11080737
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA-B*51:01, HLA-B*55:01, CYP2C9*3, and Phenytoin-Induced Cutaneous Adverse Drug Reactions in the South Indian Tamil Population

Abstract: Phenytoin (PHT) is one of the most commonly reported aromatic anti-epileptic drugs (AEDs) to cause cutaneous adverse reactions (CADRs), particularly severe cutaneous adverse reactions (SCARs). Although human leukocyte antigen (HLA)-B*15:02 is associated with PHT-induced Steven Johnson syndrome/toxic epidermal necrosis (SJS/TEN) in East Asians, the association is much weaker than it is reported for carbamazepine (CBZ). In this study, we investigated the association of pharmacogenetic variants of the HLA B gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
(58 reference statements)
1
4
0
Order By: Relevance
“…The current finding correlates with the previous report, in which both the drugs AMX and CIP displayed hepatotoxicity in an in vivo (rat) experiment [16]. The association of cytochrome P450 2C9 x 3 (CYP2C9 x 3) and human leukocyte antigen (HLA-B x 51:01) allele in phenytoin (PHT)-induced cutaneous adverse drug reactions was reported in South Indian Tamil patients [17]. The association between the human leukocyte antigen (HLA-B x 15:02) allele and carbamazepine-induced SJS was observed in Han Chinese patients [5].…”
Section: Discussionsupporting
confidence: 91%
“…The current finding correlates with the previous report, in which both the drugs AMX and CIP displayed hepatotoxicity in an in vivo (rat) experiment [16]. The association of cytochrome P450 2C9 x 3 (CYP2C9 x 3) and human leukocyte antigen (HLA-B x 51:01) allele in phenytoin (PHT)-induced cutaneous adverse drug reactions was reported in South Indian Tamil patients [17]. The association between the human leukocyte antigen (HLA-B x 15:02) allele and carbamazepine-induced SJS was observed in Han Chinese patients [5].…”
Section: Discussionsupporting
confidence: 91%
“…In a Han-Chinese population, a relationship between carbamazepine-induced Maculopapular exanthema (MPE)/Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) and HLA-B*51:01 (OR 4.56, 95 percent CI 2.0–10.5, p = 0.01) was discovered ( Hsiao et al, 2014 ). This allele association with AEDs-induced CADRs has been confirmed in North and South India ( Ihtisham et al, 2019 ; John et al, 2021 ), Japan ( Kaniwa et al, 2013 ), Thailand ( Tassaneeyakul et al, 2016 ; Manuyakorn et al, 2020 ), and among Koreans ( Kim. et al, 2016 ).…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, in the Thai population, it is also significantly associated with SCARs (such as SJS/TEN and DRESS) related to phenytoin (PHT), which is sold under the brand name Dilantin among others and is an anti-seizure medication that is useful for the prevention of tonic-clonic seizures (also known as grand mal seizures) and focal seizures (Tassaneeyakul et al, 2016). In addition, a very recent study demonstrated the association between HLA-B*51:01, HLA-B*55:01, and CYP2C9*3 and phenytoin-induced CADRs in the South Indian Tamil population (John et al, 2021). Another phenytoin-induced ADR allele is HLA-B*15:02, which also has been associated with other antiepileptic drugs, such as carbamazepine, in populations with Asian ancestry (Sukasem et al, 2018) and in the Spanish population (Ramirez et al, 2017); however, it had a rare prevalence in our study.…”
Section: Discussionmentioning
confidence: 99%